The cosmic evolution of low-luminosity radio sources from the SDSS DR1 - Clewley, L; Jarvis, M (2004)
In this paper we constrain the evolution in the comoving space density for low-luminosity (typically FRI) radio sources as a function of cosmic epoch by matching deep radio surveys (WENSS, FIRST and NVSS) with the Sloan Digital Sky Survey (SDSS). This results in 1014 matched radio sources covering an effective area of 0.217 sr, 686 with L(325 MHz) < 10^25 W/Hz/sr, which is an order of magnitude larger than any previous study at these luminosities. Using the non-parametric V/Vmax test we show that low-luminosity radio sources evolve differently to their more powerful, predominantly FRII, counterparts. Indeed, we find that the lower luminosity population is consistent with a constant comoving space density with redshift, as opposed to the strong positive evolution for the more powerful sources.